The little book of Nursery Rhymes - "NA" (London Alligator, Publishers, 2018)
The little book collection series of girls' and boys' fairy tales, bedtime stories and nursery rhymes. This small format 4 storybook edition is beautifully illustrated and content the classic favorites: Cinderella, Aladdin, Little Red Riding Hood, The Gingerbread Man and more (see the image gallery). Each hard cover colorful book contents 64 pages, totally 18 stories & 60 short rhymes!
Keywords: Nursery Rhym book